The concept of “Freespace” : architecture as care, gift, place and common good. - Bandi, Fabrizia (Scenari, 2021)
The latest International Architecture Exhibition, curated by the architects Yvonne Farrell and Shelley McNamara, was entitled “Freespace” and focused on the idea of ​​gift and gratuitousness. Architecture represents a man-made space that can be freely donated to humans. Therefore, to grasp the entire potential of this intuition, the paper discusses the concept of “Freespace” and its possible meanings, identifying three main elements that characterize the core of this idea: care, gift, and place. Finally, Freespace could also concern a public space turned into a common good, embodying a new type of place outside the dichotomy of public and private.